Review and identification of the cuckoo bees of central Europe (Hymenoptera: Halictidae: Sphecodes) - Bogusch, Petr; Straka, Jakub (Zootaxa, 2012)
We reviewed nomenclature, biology, hosts, geographical distribution and compiled an identification key for all 33 Sphe-codes Latreille, 1804 species known from central Europe. The identification key is separated for females and males andinclude 204 figures (photographs) of identification characters as well as male genitalia of all species. Taxonomically dif-ficult groups within the genus were critically studied and new characters, as well as corrected geographical distribution,are presented, i.e., the S. reticulatus group (S. alternatus Smith, 1853, S. crassanus Warncke, 1992 and S. reticulatusThomson, 1870), S. croaticus group (S. croaticus Meyer, 1922, S. pseudofasciatus Blüthgen, 1925 and S. zangherii Nosk-iewicz, 1931) and S. miniatus group (S. marginatus Hagens, 1882, S. miniatus Hagens, 1882 and S. nomioidis Pesenko,1979). The name S. nomioidis is used because it is the only available name for the taxon formerly identified as S. margi-natus in Eastern Europe. Sphecodes capverdensis Pesenko & La Roche, 2002 is considered to be a junior synonym of S.pinguiculus Pérez, 1903 (syn. nov.). In addition we summarized all known host records of Sphecodes, including a discussion of the likelihood of published data and presentation of new host data.